Bir diplomat olarak Galip Kemali Söylemezoğlu (1873-1960) - Budak, Ebru (My University, 2017)
Bu tez çalışmasında, I. ve II. Meşrutiyet, Milli Mücadele ve Cumhuriyet dönemlerinde yaşamış ve önemli görevlerde bulunmuş, diplomat ve yazar Galip Kemali Söylemezoğlu (1873-1960)’nun biyografisi ele alınmıştır.

In this thesis, the biography of author and diplomat Galip Kemali Söylemezoğlu(1873-1960), who lived in the period of Turkish National Struggle, 1 st and 2 nd constitutionalist period of Republic of Turkey and occupied important posts, has been searched studied.
Keywords: 20. yy; Author; Biyografi; Diplomat; Diplomatlar, Türk; Envoy; Galip Kemali Söylemezoğlu, (1873-1960); Sefir; Tarih; Türkiye; Yazar Biography